Influence of Control and Family Management in the Indebtedness of Brazilian Open Business: a Quantitative Study - Liliane Cristina Segura; Henrique Formigoni (BBR: Brazilian Business Review)
This research investigated the influence of the family on the debt of Brazilian open business companies. Although there is a vast national and international literature on capital structure, there are still doubts on the importance of family in business management. In Brazil, due to the large number of family businesses, it is even more evident the need to investigate the issue. The studied population was composed of companies listed on the BM&FBovespa, in 2010, and the final sample consisted of 356 companies. Six years were analyzed (2004-2009), in a total of 2,136 observations. The results show that the studied companies that are familiar or that have family management have become less indebted than others. This result is in accordance with national and international studies, according to which family firms tend to be more conservative in their investments, seeking to use more equity than third party capital.